2022
DOI: 10.1186/s12864-022-08632-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex determination locus in sea cucumber Apostichopus japonicus using genome-wide association study

Abstract: Background Sex determination mechanisms are complicated and diverse across taxonomic categories. Sea cucumber Apostichopus japonicus is a benthic echinoderm, which is the closest group of invertebrates to chordate, and important economic and ecologically aquaculture species in China. A. japonicus is dioecious, and no phenotypic differences between males and females can be detected before sexual maturation. Identification of sex determination locus will broaden knowledge about sex-determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Another study reported the first high-quality, chromosome-level genome assembly of Holothuria leucospilota , an ecologically significant sea cucumber species with a prototypical Cuvierian organ (CO), that is a defensive organ with bioadhesive properties [ 35 ] The H. leucospilota genome reveals characteristic long-repeat signatures in CO-specific proteins, analogous to fibrous proteins of disparate organisms, including spider spidroin and silkworm fibroin, offering new insights into the molecular features and evolution of this unique defensive organ. Likewise, integrated genome-wide association study (GWAS) and the analysis of the distribution of characteristic sex-specific SNPs have clarified sex determination mechanisms and identified sex-linked markers, showing that multiple sex-associated loci are located on several chromosomes in A. japonicus [ 158 ].…”
Section: Genomic-transcriptomic Information and Cellular And Molecula...mentioning
confidence: 99%
“…Another study reported the first high-quality, chromosome-level genome assembly of Holothuria leucospilota , an ecologically significant sea cucumber species with a prototypical Cuvierian organ (CO), that is a defensive organ with bioadhesive properties [ 35 ] The H. leucospilota genome reveals characteristic long-repeat signatures in CO-specific proteins, analogous to fibrous proteins of disparate organisms, including spider spidroin and silkworm fibroin, offering new insights into the molecular features and evolution of this unique defensive organ. Likewise, integrated genome-wide association study (GWAS) and the analysis of the distribution of characteristic sex-specific SNPs have clarified sex determination mechanisms and identified sex-linked markers, showing that multiple sex-associated loci are located on several chromosomes in A. japonicus [ 158 ].…”
Section: Genomic-transcriptomic Information and Cellular And Molecula...mentioning
confidence: 99%
“…Compared with other echinoderms ( Supplemental Table S3 ), the repetitive gene percentage of C. heheva (Kairei vent) in this study is more than that in the Haima cold seep (56.64%) [ 21 ] and only less than that of Paelopatides sp. Yap (73.93%) [ 23 ], and the percentage of shallow water A. japonicus is only 27.20% [ 55 , 64 ]. After repeat masking, protein-coding genes annotated used a combination of ab initio , homology-based, and transcript evidence–predicted approaches, and a total of 32,434 were successfully identified (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chromosome-level genome in our study of C. heheva (CHEH_vent1.0) and A. japonicus (AJH1.0) [ 55 ] was selected as comparisons for syntenic analysis. BLAST version 2.9.0 (BLAST Similarity Search, RRID:SCR_008419 ) with parameter “-evalue 1e-10” was used to identify similar gene pairs [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The positions of TRP genes on the chromosomes were determined by annotations based on the genome database (China National GeneBank DataBase (CNGBdb) under BioProject Accession No. CNP0002776) and mapped by TBtools software (Chen et al, 2020;Wang et al, 2022b). To further investigate the relationship of AjTRPs with those from other representative species, ClustalW was used to make multiple sequence alignments of full-length proteins and the phylogenetic analysis based on the Maximum Likelihood method were performed using MEGA 11 with WAG+G+I+F model and then edited with EvolView (https://evolgenius.info// evolview-v2/).…”
Section: Sequence Analysis and Number Comparisons Of Trp Genes And Ph...mentioning
confidence: 99%